Oryzomys palustris (Rodentia: Cricetidae) - Rose, Robert K. (Mammalian species, 2023)
Oryzomys palustris (Harlan, 1837), the common marsh rice rat, is an Oryzomyine rodent with a tail nearly as long as the head and body, grayish above and white below with long-toed white feet. This account is an update of Mammalian Species 176 on the subject species by James L. Wolfe (1982a), incorporating 103 new references, most published since 1982. Oryzomys palustris, one of six living and two extinct species in this Neotropical genus, is semiaquatic and omnivorous, being highly carnivorous in some populations. It is parapatric with O. texensis in the western portion of its distribution in the southern United States. Oryzomys palustris is classified as “Least Concern” (LC) on the International Union for Conservation of Nature Red List.